Towards New Web Application Development Practices - Poulymenakou, Angeliki; Drakos, William; Papazafeiropoulou, Anastasia; Doukidis, Georgios (Australasian Journal of Information Systems, 1998)
Electronic Commerce over the Internet, aims to become a global conveyor belt of business transactions. Web applications of increasing sophistication emerge in almost every business sector, reflecting a variety of technical and technological approaches. In this paper we argue that system developers need to reconsider their professional practices in the context of these new technologies by taking advantage of opportunities like short response cycles and easy diffusion of systems results, while they recognise the limitations of traditional practice. We discuss a framework of IS development issues for Internet based applications and propose guidelines towards new development practices.